Ethernet Communication Platform for synthesized devices in Xilinx FPGA - Souza, Rodrigo Neri de (2011)
This article presents and describes the implementation of an Ethernet communication platform for devices synthesized into Xilinx FPGAs. This platform provides a way to control programmable logic devices, as well as data communication using a standard network. The proposed solution is very complete and provides common services and protocols of TCP/IP stack, in order to provide maximum flexibility. The platform modularity allows its use by most devices that can be synthesized into a FGPA, providing they adhere to the required implementation directives (FIFO communication). Presently the proposed platform is being used for the implementation of a remotely accessible, and IEEE1149.1 compatible, digital tester. The design is based on a traditional embedded system (software and hardware) also synthesized into the FPGA. The embedded system hardware is based on a MicroBlaze microprocessor (softcore) and implemented using XPS. It runs the Petalinux embedded operating system and custom developed applications.